The importance of person-centred care and how to achieve it. Issue 7 (2nd August 2021) - Stonehouse, David
Abstract : This article discusses the important concept of person-centred care and how this can be achieved. Following an introduction defining what is meant by this term and contrasting it with the term patient-centred care, the relevant and pertinent parts of the Nursing and Midwifery Council code will then be identified and discussed. The four principles of person-centred care will then be presented. The role of the support worker and nursing associate will be made clear in how the wishes and needs of patients can be gained. Self-awareness, emotional intelligence and communication will be discussed in relation to this. Finally, two potential barriers to the successful achievement of person-centred care will be identified.